Karakterisasi Jeroan Ikan Cakalang sebagai Skrining Awal Bahan Baku Perangkap Lalat Rumah Musca domestica dan Antibakteri: Characterization of Skipjack Viscera as Initial Screening of Sources for Housefly Traps Musca domestica and Antibacterial - Rahmatia Garwan; Harsi Kusumaningrum; Tati Nurhayati; Hanifah Nuryani Lioe (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Viscera of skipjack tuna which is rich in protein has the potential as a source of Musca domestica house fly trap-compounds as well as a source of antibacterial. This study aims to explore the potential of skipjack viscera in the form of stomach, intestines, liver and the mixtures as a source of house fly traps and antibacterial components. Skipjack viscera were stored for 2 days at room temperature. Moisture content, protein, TVB, amino acids, fly trap activity and antibacterial activity were then analyzed. The results showed that the water content, fat and TVB of all parts of skipjack viscera increased, while the protein content decreased during 2 days of storage. The water content ranged from 73,90% wb to 85,19% wb. Protein content was found from 14,46% wb to 18,07% wb. Fat content ranged from 0,95% wb to 2,71% wb, while TVB levels ranged from 64,74 mg N/100 g to 133,92 mg N/100 g. The main amino acid composition of skipjack viscera was glutamic acid, arginine, glycine, phenylalanine, tyrosine, lysine, serine, valine and histidine. The increase in TVB levels after 2 days of storage was associated with the highest activity of stomach viscera in trapping flies with an average of 13.50 flies. The greatest bacterial growth inhibition was showed by the mixture of viscera on day 0 at a concentration of 75% against Staphylococcus aureus and Escherichia coli, i.e., 9.30 mm and 8.78 mm zone of inhibition, respectively. The antibacterial activity against both bacteria was classified as a moderate. Flies-trapping and antimicrobial compounds are likely closely related to the amino acid composition of skipjack viscera. More in-depth research on the role of amino acids as the main component of flies-trapper and antimicrobial of skipjack viscera is the subject of further research.